Legal Policy of President Joko Widodo and the Independence of Constitutional Court: Politik Legislasi Presiden Joko Widodo dan Independensi Mahkamah Konstitusi - Arizona, Yance (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
This article discusses the independence of the Constitutional Court in reviewing legislation created by President Joko Widodo. There are three main questions posted: What is the character of legal policy under President Joko Widodo, how has the role of the Constitutional Court shifted in the last decade and what is the character of the Constitutional Court’s decisions in reviewing legislation enacted by President Joko Widodo. These questions are discussed using normative research on Constitutional Court decisions. Data from the results of this research are deployed quantitatively and qualitatively. Quantitative data is displayed to show legislative trends and Constitutional Court decisions. Analysis was carried out on 78 laws and 277 Constitutional Court Decisions. Meanwhile, qualitative research is to assess the character of legislation and Constitutional Court decisions through case studies of several Constitutional Court decisions related to politics, economics, law enforcement institutions and civil liberties. This article shows that the Constitutional Court has not been effective in exercising judicial review of legislation enacted under President Joko Widodo, amidst an increasingly abusive legislative process.